MPIA as a Stopgap Measure: Tackling the Stagnation in the WTO Dispute Settlement System - Pawestri Nindyatami; Helsa Yohana Marela Graceyela (Faculty of Law, Universitas Jenderal Soedirman, 2025)
The paralysis of the World Trade Organization’s (WTO) Appellate Body (AB) in 2019 created a significant gap in the organization’s Dispute Settlement Mechanism (DSM), undermining its ability to enforce fair and timely resolutions for trade disputes. In response, the Multi-Party Interim Appeal Arbitration Arrangement (MPIA) emerged as a temporary, voluntary solution for WTO members seeking an alternative appellate mechanism. This paper explores the structure, processes, and implications of the MPIA, comparing it to the AB system to assess whether it offers a viable, efficient substitute. The study examines how MPIA’s arbitration-based approach and voluntary membership differ from AB’s mandatory, judicial review framework. Findings suggest that while MPIA provides flexibility, timeliness, and procedural efficiency, its limited membership and provisional nature present challenges to achieving consistency in dispute resolution. As WTO members continue to negotiate a path forward for the DSM, the MPIA serves as a testament to multilateral adaptability and highlights the potential role of arbitration in global trade governance. This analysis contributes to the ongoing discourse on WTO reform, emphasizing the need for a durable, balanced mechanism that meets both current efficiency demands and long-term objectives for fairness and consistency in international trade. Keywords: MPIA; WTO; DSM.